Association between Type 2 Diabetes Mellitus and Risk of Development of Oral Cancer: A Systematic Review and Meta-analysis - Anagha Kabra; Amar Kumar Shaw; Sakshi Kanjalkar; Aditi Panchal; Pradyumna Kumar Sahoo; Arti Gachake (Journal of Head & Neck Physicians and Surgeons)
Aim: To assess the risk of developing oral cancer (OC) in individuals who have diabetes mellitus (DM) and to predict the prognosis for OC patients with DM. Methodology: The review adhered to Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) 2020 guidelines and was registered in PROSPERO (CRD42024517197). A thorough search of databases was conducted from January 2000 to May 2024 to identify studies reporting the reporting association between DM and the development of OC. Quality assessment was performed using the Newcastle Ottawa Scale for included studies. The odds ratio (OR) and risk ratio (RR) served as the summary statistic measure, employing a random-effect model with a significance threshold set at P < 0.05. Results: Twelve studies met the eligibility criteria and underwent qualitative synthesis, with eight studies in meta-analysis. Upon quality assessment, the studies demonstrated a range of moderate to low risk of bias (ROB), ensuring a comprehensive evaluation of the evidence base. Meta-analysis showed that individuals with type 2 diabetes mellitus had a higher shown high association (OR = 2.07 (0.52–8.18) and risk (RR =1.31 (0.70–2.43) for the development of OC compared to nondiabetics (P > 0.05). The funnel plot did show presence of possible publication bias in meta-analysis. Conclusion: It was found that DM patients were at higher risk and more associated with the development of OC. However, as OC is multifactorial disease, the presence of a single factor cannot have a significant effect on disease progression. Therefore, furthermore prospective studies with a greater sample size and follow-up period should be conducted so as to validate the findings of this study.